Mechanism of Y2O3 as heterogeneous nucleus of TiC in hypereutectic Fe-Cr-C-Ti-Y2O3 coating: First principle calculation and experiment research. (December 2017) - Shi, Zhijun; Liu, Sha; Gao, Yukui; Zhou, Yefei; Xing, Xiaolei; Ren, Xuejun; Yang, Qingxiang
Graphical abstract: Abstract: The lattice misfit between Y2 O3 and TiC low index faces was calculated by the Bramfitt two-dimensional lattice misfit theory in this work. The interface electronic structure, adhesive work and interfacial energy of Y2 O3 (111)/TiC(110) interfaces were calculated by the first principles method. The interfacial bonding characters were analyzed by the interface charge density, electron density difference and mulliken populations. The microstructure of the hypereutectic Fe-Cr-C-Ti-Y2 O3 coating was observed by field emission scanning electron microscopy (FESEM) and transmission electron microscopy (TEM). The calculational results show that, the lattice misfit of Y2 O3 (111)/TiC(110) interface is 8.6%, which meets that Y2 O3 acts as medium effective heterogeneous nucleus of TiC. Four interface models have been constructed according to the surficial termination situations and interfacial atomic stacking modes, in which O-TiC2 interface is most stable. Its interface adhesive work is the largest (6.07 J/m 2 ) and its interfacial energy is the smallest (−1.22 J/m 2 ). And its interfacial bonding is a mixture of polar covalent, metallic and electrovalent bonds, which proves that Y2 O3 and TiC can form a stable interface. The experimental results show that, Y2 O3 particle exists in the core of the flower-like TiC particle in the hypereutectic Fe-Cr-C-Ti-Y2 O3 coating and they are combined tightly, which proves that Y2 O3 can act as the heterogeneous nucleus of TiC.